A preliminary discussion on Malaysian Chinese literature studies in Chinese mainland: taking literatures in Chinese as an example - Wang, Jiaqi; Lim, Choon Bee (Universiti Putra Malaysia Press, 2022)
In the academic circle in the Chinese mainland, Malaysian Chinese literature studies closely connect China with the world as a part of World Chinese-language literature. However, due to the isolation of the Chinese mainland from Malaysia after the Second World War, the interruption of thirty-year communication directly or indirectly led to some problems within academic circles in the Chinese mainland about studying Malaysian Chinese literature. Taking the journal of Literatures in Chinese as an example, this paper attempts to explore the focus and its underlying causes of the academic study on Malaysian Chinese literature in the Chinese mainland through data statistics and comparison. The following results were obtained: the low attention paid to the Malaysian Chinese literature studies, fewer relevant research journals with limited and single content, regionally weakened distribution of journals and authors from South to North and from East to West, and lacking experience and originality in the part of author teams.